Optimization and electro chemical grinding surface investigation on eglin steel. (2022) - Kannan, G.R.; Vijayakumar, B.; Senthil, T.S.; Sunagar, Prashant; Ranjith Kumar, R.; Parida, Lukesh; Subbiah, Ram
Highlights: The present investigation is used to analyze the surface of ECG of eglin steel. The grinding wheel speed, voltage and flow rate are used to evaluate the rate of metal removal. The desirable rate of metal removal was found through taguchi technique. The parametric effect and their role were investigated through variance analysis. The grinding surface of the eglin steel was analyzed through atomic force microscopy. The surface texture was also studied through surface roughness plot. Abstract: Surface technology is playing an essential role in metal industries to enhance the surface texture. The present investigation is used to analyze the surface of electro chemical grinding (ECG) of eglin steel. The methodology of the present work is to optimize the ECG process factors and analyze the machined surface. The grinding wheel speed, voltage and flow rate are used to evaluate the rate of metal removal. The desirable rate of metal removal (RMR) was found through taguchi technique. The parametric effect and their role were investigated through variance analysis. The grinding surface of the eglin steel was analyzed through atomic force microscopy. The surface texture was also studied through surface roughness plot. The optimal metal removal rate was performed at 15 V of voltage, 9 LPM of electrolyte flow rate and grinding wheel speed of 1400 rpm. The effect of voltage, flow rate and grinding wheel speed are 75.10%, 21.17% and 2.755% respectively. The average roughness of the electro chemical grinding surface is 24.15 nm. It was concluded that surface obtained from ECG was better than other process.